Traditional Rites As A Hybrid Accountability Mechanism In Local Financial Supervision: The Relevance Of Bau Lolon In East Flores - Lamawuran, Yosef Dionisius; Peten, Yasinta Yunrianto Palan; Kelen, Veronika Boleng; Welin, Elisabeth Date Masan; Medho, Yohana Fransiska (Universitas Riau Kepulauan, 2026)
The weakness of formal accountability mechanisms in local financial governance has led to the persistence of customary-based oversight practices in various local communities, including the Bau Lolon ritual in East Flores. Using an ethnographic qualitative approach, this study employs in-depth interviews, participant observation, and analysis of official documents and customary archives to examine how Bau Lolon functions as a hybrid accountability mechanism. The findings reveal that Bau Lolon functions as both a living law and a traditional integrity pact that binds public officials, contractors, and the community through a cosmic contract believed to carry non-negotiable spiritual consequences. Field findings indicate that this ritual is employed in oaths of office, oversight of development funds, and the resolution of accountability conflicts, thereby providing a moral infrastructure of governance that complements the shortcomings of formal law. This study concludes that Bau Lolon is an instrument of indigenous public administration that affirms the role of customary law in strengthening the integrity of public governance. This study recommends the need for further exploration through mixed-methods approaches and cross-cultural comparative studies to strengthen the empirical basis and expand the global relevance of the concept of ritual-based hybrid accountability.